THE GRAIN QUALITY INDICATORS OF BUCKWHEAT - Isroilov Bakhtiyor, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract. This study evaluated the effect of sowing date and planting method on buckwheat grain quality when cultivated as a second crop. Results showed that delayed sowing reduced grain uniformity by 1-4%. Optimal uniformity (84%) was achieved with early sowing (June 20) using a single‑row method at 1 million seeds/ha, whereas the lowest (80%) resulted from late sowing (July 10) with a triple‑row method at 3 million seeds/ha. Similarly, grain test weight was highest (472 g/l) under early sowing with single-row planting and lowest (465 g/l) under late sowing with high-density triple-row planting. The findings demonstrate that early sowing with moderate plant density is crucial for maximizing both grain uniformity and test weight in second-crop buckwheat.